2019
DOI: 10.1208/s12249-018-1263-1
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of Lidocaine Microemulsions for Transdermal Delivery

Abstract: Topical administration is a preferable choice for local anesthetic delivery. Microemulsions have shown great effectiveness for transdermal transport of lidocaine. However, fabrication of microemulsions containing highly concentrated lidocaine (10%) to provide an extended local anesthetic effect is still a challenge. This study investigated the feasibility of using microemulsions for transdermal delivery of a high dosage of lidocaine (10%). At first, eutectic mixtures by kneading lidocaine with thymol were tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Additionally, they are favorable for their ease of preparation. Moreover, it is proposed that their use for transdermal drug delivery enhances the permeability profile due to the smaller droplet size which increases the contact with the membrane improving the delivery of the encapsulated drug [ 55 , 56 ]. However, it has been reported that nanoemulsions achieve a higher degree permeation and drug loading capacity as compared with microemulsions [ 10 , 25 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, they are favorable for their ease of preparation. Moreover, it is proposed that their use for transdermal drug delivery enhances the permeability profile due to the smaller droplet size which increases the contact with the membrane improving the delivery of the encapsulated drug [ 55 , 56 ]. However, it has been reported that nanoemulsions achieve a higher degree permeation and drug loading capacity as compared with microemulsions [ 10 , 25 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The solution was then filtered and kept in Franz cell to assess permeation profile. It is noticed that the use of nanoemulsion formulation produced an enhanced permeation as compared with the saturated solution which could be attributed to the nano-sized droplets which would have an increased surface area that can increase the contact of the encapsulated drug with the stratum corneum producing improved permeability for transdermal delivery [ 55 ]. As discussed earlier, the change in flux could be as a result of the interactions between the surfactant and membrane or the drug and surfactant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data indicate that surfactants enhance the transdermal delivery of LidH-loaded vesicles [ 12 , 30 , 31 ]. The results of this study showed that ENL formulations deliver significantly more LidH in 6 h than SLN formulations, probably because the surfactants effectively decrease the surface tension at the interface of oil and water, and ENLs can readily deform during diffusion [ 31 ]. This characteristic facilitates a deep diffusion of ENL in the skin and LidH release.…”
Section: Discussionmentioning
confidence: 99%
“…( 41 42 ) and Wang et al . ( 43 ). This could be explained by the differences in the microemulsion composition and by the penetration enhancement effect of jojoba oil itself.…”
Section: Discussionmentioning
confidence: 99%